Control of elemental impurities in herbal medicines - A. P. Baula; Т. М. Derkach (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The standardisation of plant raw materials is among the most important problems of the production of herbal medicines. Medicinal plant raw materials are of complex nature and can be contaminated with impurity elements. Therefore, the content of elemental impurities typical for plants should be controlled in comparison with the existing conceptions of recommended or permitted daily exposures of human consumption of some chemical elements. The paper goal was to study the existing approaches in the world to the fixing of elemental impurity content in herbal medicines and comparative analysis of their permitted daily exposures. The following methods were used to implement the research goal: system approach, bibliographic and information search, statistical methods, as well as generalisation and analysis. The work is based on the analysis of documents of World Health Organisation and appropriate organisations of leading countries. The contents of 28 elements were shown to normalise in these documents. Depending on their toxicity and probability of ingress into drugs, the elements are divided into four classes. This approach creates a clear idea of the potential effects of elements on the human organism and also illustrates the sensitivity requirements for analytical methods to be used for elemental control. In medicinal plants as well as in plants that are used as food additives and spices, the content of the five most toxic elements (As, Hg, Cd, Pb and Cr) is fixed. For other impurities in medicinal plants, there are no universally recognised limit values in contrast to medicinal products. Therefore, when analysing the quality of herbal medicines, one should take into account permitted daily exposures of human consumption of individual chemical elements used for the quality control of foodstuff and drinking water as well as environmental protection.